Cervico-Vaginal Inflammatory Cytokine and Chemokine Responses to Two Different SIV Immunogens - Toledo, Nikki P. L.; Li, Hongzhao; Omange, Robert W.; Dacoba, Tamara G.; Crecente-Campo, Jose; Schalk, Dane; Kashem, Mohammad A.; Rakasz, Eva; Schultz-Darken, Nancy; Li, Qingsheng; Whitney, James B.; Alonso, Maria J.; et al. (Frontiers in Immunology, 2020)
Studies have shown that vaccine vectors and route of immunization can differentially activate different arms of the immune system. However, the effects of different HIV vaccine immunogens on mucosal inflammation have not yet been studied. Because mucosal sites are the primary route of HIV infection, we evaluated the cervico-vaginal inflammatory cytokine and chemokine levels of Mauritian cynomolgus macaques following immunization and boost using two different SIV vaccine immunogens. The PCS vaccine delivers 12 20-amino acid peptides overlapping the 12 protease cleavage sites, and the Gag/Env vaccine delivers the full Gag and full Env proteins of simian immunodeficiency virus. We showed that the PCS vaccine prime and boosts induced short-lived, lower level increases of a few pro-inflammatory/chemotactic cytokines. In the PCS-vaccine group only the levels of MCP-1 were significantly increased above the baseline (P=0.0078, Week 6; P=0.0078, Week 17; P=0.0234; Week 51) following multiple boosts. In contrast, immunizations with the Gag/Env vaccine persistently increased the levels of multiple cytokines/chemokines. In the Gag/Env group, higher than baseline levels were consistently observed for IL-8 (P=0.0078, Week 16; P=0.0078, Week 17; P=0.0156, Week 52), IL-1β (P=0.0234, Week 16; P=0.0156, Week 17; P=0.0156, Week 52), and MIP-1α (P=0.0313, Week 16; P=0.0156, Week 17; P=0.0313, Week 52). Over time, repeated boosts altered the relative levels of these cytokines between the Gag/Env and PCS vaccine group. 18 weeks after final boost with a higher dosage, IP-10 levels (P=0.0313) in the Gag/Env group remained higher than baseline. Thus, the influence of vaccine immunogens on mucosal inflammation needs to be considered when developing and evaluating candidate HIV vaccines.